EDUKASI TENTANG KOLESTEROL PADA IBU PKK DESA PADDINGING KECAMATAN SANROBONE KABUPATEN TAKALAR - Amirah, Sitti; Kosman, Rachmat; Fitriana; Rahman, Safriana; Rusli; Putra, Bayu; Nuryanti, Siska; Harly Nurung, Ayyub (JURNAL PENGABDIAN FARMASI DAN SAINS, 2023)
Cholesterol is a lipid compound needed by the body as an essential component of cell membranes, hormone synthesis, energy sources and other needs. The body needs lipids in moderate amounts, the average adult's cholesterol requirement is around 1100 mg of cholesterol/day. About 25-40% of cholesterol needs are obtained from food and the rest is obtained from synthesis by the body. High cholesterol levels can trigger atherosclerosis, hardening and narrowing of the arteries which can lead to various diseases such as ischemia, stroke, heart attack. By looking at the daily life of the people in Paddinding village, kec. Sanrobone, where the majority of farmers are farmers, allows the public to ignore information about health, so education is needed to improve public health status. This activity is carried out using lecture and discucussion methods that are focused on providing understanding to the public about cholesterol, what is the role of cholesterol in the body, sources of cholesterol, how to prevent and deal with cholesterol disorders. Community service activities carried out are one of the means to increase public knowledge about how to prevent and treat cholesterol disorders.